PENGARUH DISIPLIN KERJA, BUDAYA ORGANISASI TERHADAP PROFESIONALISME GURU (Studi Pada Guru MTsN 2 Sumenep) - Rahmawati; Woro Utari; Chamariyah Chamariyah (EKONOMIKA45 : Jurnal Ilmiah Manajemen, Ekonomi Bisnis, Kewirausahaan, 2020)
This type of research is explanatory research, the research approach uses a quantitative approach, data analysis uses SPSS. The research sample was 40 teachers. The objectives of this study are 1). To analyze and analyze the effect of work on teacher professionalism 2). To analyze and analyze the organization whether the organization has a partial and significant effect on teacher professionalism 4). To analyze and analyze the organization whether the organization has a simultaneous and significant effect on teacher professionalism 5). To analyze and analyze work stress, organizational culture, has a simultaneous influence on professionalism of MTsN 2 Sumenep teachers. The results showed that: 1). Simultaneously, work discipline, organizational culture, have a significant effect on professionalism for MTsN 2 Sumenep teachers. Evidenced by the results of the calculated F value of 4.627 with a known significance level of the value of 0.004 (less than 0.05). 2). Partially, competence, compensation and creativity have a significant effect on teacher professionalism for 'teachers at MTsN 2 Sumenep. 3). Based on the test results, it is known that organizational culture has an effect on the performance of employees of MTsN 2 Sumenep teachers; as evidenced by the t value is 4,829 with a significance level of 0.003 (less than 0.05).